2017
DOI: 10.1002/jctb.5231
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the removal of hazardous pollutants from coke‐making wastewater by dosing activated carbon to a pilot‐scale activated sludge process

Abstract: BACKGROUND: Powdered activated carbon (PAC) was investigated for its ability to remove six polycyclic aromatic hydrocarbons ( 6PAHs) (fluoranthene, benzo[b + J]fluoranthene, benzo[k]fluoranthene, benzo[a]pyrene, indeno[1,2,3-cd]pyrene, benzo[g,h,i]perylene), trace metals and colour from coke-making wastewater when dosed to a pilot-plant activated sludge process (ASP). The ASP had a volume of 0.68 m 3 and was operated to simulate the full-scale ASP treating coke wastewater from a steel works. Operational condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
2
7
1
Order By: Relevance
“…Burmistrz and Burmistrz (2013) reported 255-312 µg/L for the sum of 16 PAHs whilst Zhang et al (2012a) reported much higher concentrations of 5470 ± 907 µg/L for the sum of 18 PAHs. Raper et al (2017) reported the sum of 6 PAHs at 179 ± 35 µg/L therefore being more comparable to the values reported by Burmistrz and Burmistrz (2013). Trace metals have been reported at 4216 µg/L (Raper et al, 2017).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Burmistrz and Burmistrz (2013) reported 255-312 µg/L for the sum of 16 PAHs whilst Zhang et al (2012a) reported much higher concentrations of 5470 ± 907 µg/L for the sum of 18 PAHs. Raper et al (2017) reported the sum of 6 PAHs at 179 ± 35 µg/L therefore being more comparable to the values reported by Burmistrz and Burmistrz (2013). Trace metals have been reported at 4216 µg/L (Raper et al, 2017).…”
Section: Introductionsupporting
confidence: 77%
“…Raper et al (2017) reported the sum of 6 PAHs at 179 ± 35 µg/L therefore being more comparable to the values reported by Burmistrz and Burmistrz (2013). Trace metals have been reported at 4216 µg/L (Raper et al, 2017).…”
Section: Introductionsupporting
confidence: 77%
“…Coke wastewaters are typically characterized by ammonia concentrations of 50–500 mg L –1 , thiocyanate (SCN – ) concentrations of 100–400 mg L –1 and phenol concentrations of 60–400 mg L –1 . The sum of six polycyclic aromatic hydrocarbons (Σ6PAHs: sum of fluoranthene, benzo[b]fluoranthene, benzo[k]fluoranthene, benzo[a]pyrene, indeno[1,2,3‐cd]pyrene and benzo[g,h,i]perylene) was previously reported at 179 ± 35 µg L –1 . Total trace metals (sum of Al, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Cd and Pb) also were reported at a concentration of 4216 µg L –1 with individual trace metal concentrations ranging from 0.13 µg L –1 (Cd) to 3612 µg L –1 (Fe) .…”
Section: Introductionmentioning
confidence: 99%
“…Coking wastewater is produced during the coke‐making process, and bio‐treatment effluent still contains a certain level of bio‐refractory organics . These include PAHs, heterocyclic compounds and long‐chain alkanes, which pose hazardous threats to the environment, when the effluent is used for coke quenching and gas washing .…”
Section: Introductionmentioning
confidence: 99%
“…Coking wastewater is produced during the coke-making process, and bio-treatment effluent still contains a certain level of bio-refractory organics. 1,2 These include PAHs, heterocyclic compounds and long-chain alkanes, which pose hazardous threats to the environment, when the effluent is used for coke quenching and gas washing. 3,4 The character of these recalcitrant organic contaminants (ROC) may also lead to the generation of disinfection byproducts and/or serious membrane fouling in the advanced treatment process.…”
Section: Introductionmentioning
confidence: 99%